PENGARUH KUALITAS LAYANAN DAN INOVASI TERHADAP CITRA PERUSAHAAN DAN LOYALITAS NASABAH PADA PT. BANK RIAU KEPRI (Jurnal Tepak Manajemen Bisnis, 2015)
Abstract. This study aimed to analyze the quality of service and innovation to the corporate image andcustomer loyalty at PT. Bank Riau Riau Islands. The instrument used for data collection was aquestionnaire. The study population was all customers of PT. Bank Riau Riau Islands who have savings,current accounts or deposits, amounting to 421 545 people. The sample in this study was obtained 196people. Data were analyzed using SEM analysis. The calculations show that the quality of service has adirect effect significant and positive impact on company image, innovation has a direct effect notsignificant and positive impact on Corporate Image, Quality of Service has a direct effect significant andpositive impact on Customer Loyalty, Innovation has no significant direct effect and positive impact onCustomer Loyalty, Corporate Image has a direct influence significant and positive impact on theCustomer Loyalty.Keywords: Quality of Service, Innovation, Corporate Image and Customer Loyalty.